Feminist ethnography, deportability and gender-based violence: accessing situated knowledge of women asylum seekers in Spain - Cortés Maisonave, Almudena (Research methods in deportation, 2024)
This chapter examines the deportability of asylum seekers in Spain from the perspective of feminist and gender anthropology. We explore the importance of a feminist ethnographic methodology in analysing the experiences of women at risk of deportation and in understanding the frameworks and contexts in which their plans and expectations are situated from a broader power-knowledge perspective. Feminist ethnography comes with significant methodological and epistemological challenges. The fieldwork for this study was conducted in Madrid (Spain) between 2014 and 2021. Using a series of different strategies and techniques, feminist ethnography allowed us to establish reciprocal relationships with women seeking asylum, professionals, organisations and activists. Our positioning as researchers was based on epistemologically establishing trusting, symmetrical relationships with the aim of centring the perspectives of women seeking asylum and their own reflections on their experiences in our analysis.